(untitled) (Research, Society and Development, 2022)
The objective of this work was to determine the influence of natural (marigold flower extract) and synthetic (canthaxanthin) pigments on the shelf life of eggs from light laying hens in the final stages of production. 288 birds were distributed in a completely randomized design, with eight treatments, consisted in four levels of marigold flower extract (2.1; 2.4; 2.7 and 3 ppm) and four levels of canthaxanthin (0.4 ; 0.7; 1,0 and 1.3 ppm), each treatment with six replicates of six birds/experimental unit. In the last ten days of the experimental period (75-78 weeks of age) a total of 960 eggs were collected, selected and randomly distributed, which 480 eggs were stored at ambient temperature and 480 under refrigeration. Ten different storage periods were analyzed (0, 5, 10, 15, 20, 25, 30, 35, 40, and 45 days), one egg each repetition (six eggs per treatment). Internal and external quality parameters were evaluated in the eggs. Egg yolk color was evaluated using the La Roche colorimetric fan (LCR), showing a significant interaction between canthaxanthin level and storage period. Yolk height (YH), albumen percentage (%A) and yolk percentage (%Y) showed significant interaction between marigold flower level and storage period. It is concluded that the use of natural (marigold flower) and synthetic (canthaxanthin) pigments for the shelf life of eggs from hens in the final stage of production did not influence most of the egg quality variables in the present study, however, eggs stored in a refrigerated environment had better results for egg conservation.